DNA Methylation of ABC Transporters Differs in Native and Non-native Populations of Conyza canadensis L. - Shah, Ambreen Tahir; Reshi, Zafar A.; Altaf, Mohammad (Frontiers in Ecology and Evolution, 2022)
While differences in methylation patterns of ABC transporters under different environmental conditions and their role in plant growth, development, and response to biotic and abiotic stress are well documented, little is known about the variation in the methylation patterns of plant species in native and non-native ranges. Here we present the results of differences in methylation of ABC transporters of Conyza canadensisL. in its native (North America) and non-native (Kashmir Himalaya) ranges. The ABC transporter genes are highly expressed in the non-native range, but its molecular mechanism is not fully understood. Our data shows that the promoter regions of ABC transporter genes have reduced DNA methylation in non-native range. Further, we found that ABC transporter genes have enriched RNA Pol II binding and reduced nucleosome occupancy, both hallmarks of transcriptional activity, in the non-native range. Our data uncovers that epigenetic changes and changes in chromatin structure are responsible for increased expression of ABC transporter genes under conditions encountered by the species in the non-native range. This study hints towards possible molecular mechanism that contribute to invasiveness of this species in non-native Kashmir Himalayan range and could pave way for further studies to better explain the enigmatic plant invasions.